Studi Deskriptif Kualitatif Dampak Lingkungan dan Tinjauan Hukum pada Usaha Laundry Koin di Kemendung, Taman, Sidoarjo - Winda Angelia Ritanti; Nur Qoilun (CV. ITTC INDONESIA, 2026)
This study aims to describe the environmental impacts and legal review of coin laundry businesses in Kemendung, Taman District, Sidoarjo Regency. The method used is a qualitative descriptive approach through observation and literature study. The results show that coin laundry businesses are a technological innovation in the service sector that provide convenience and efficiency for the community in laundry activities. However, this activity generates wastewater containing detergents and other chemicals that have the potential to pollute the environment if not properly managed, as it is generally discharged directly into drainage systems without prior treatment. From an environmental law perspective, wastewater management is regulated under Law No. 32 of 2009 concerning Environmental Protection and Management and Government Regulation No. 22 of 2021, which require every business actor to prevent environmental pollution and comply with wastewater quality standards. Therefore, coin laundry businesses still have a responsibility in managing their wastewater in order to prevent negative impacts on the surrounding environment.